Implementation of Integrated Entrepreneurship Development Policy for Business Actors in the Administrative City of East Jakarta - Yolanda Isroyanti; Izzatusolekha; Rahmat Salam (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The involvement of MSMEs in the country's economic development has significant benefits for economic growth. The development of MSMEs is one of the commitments of the Indonesian Government because MSMEs are considered to be one of the supporters of the country's GDP. However, MSME business actors still face obstacles in understanding the benefits of using technology for their businesses, including digital technology. This research then aims to see how the implementation of integrated entrepreneurship development policies occurs in East Jakarta. This research was carried out using a descriptive qualitative approach. The data obtained in this research came from interviews, observation, and documentation. The results of this research then found that the policy standards and targets refer to DKI Jakarta Gubernatorial Regulation Number 2 of 2020 but do not specifically regulate the use of digital media. The resources used in the integrated entrepreneurship development policy are 8 entrepreneurship assistants. The government provides technical and non-technical training. The government is socializing the use of digital media among business actors. Coordination is carried out in stages up to the sub-district level. The use of digital media has an impact on aspects of increasing income, increasing digital literacy, and changing policies.